1995
DOI: 10.1038/ki.1995.453
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year follow-up of a randomized study with methylprednisolone and chlorambucil in membranous nephropathy

Abstract: The natural course of idiopathic membranous nephropathy is variable, with some patients slowly progressing to renal failure while others maintain normal renal function over the entire time. Whether to treat this disease or not is controversial due to the lack of controlled data about the long-term effects of treatment. We updated at 10 years the results of a controlled trial in which 81 patients with idiopathic membraneous nephropathy and nephrotic syndrome were randomly assigned to receive symptomatic therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
226
4
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(246 citation statements)
references
References 19 publications
9
226
4
7
Order By: Relevance
“…A survey of all such trials reported between 1979 and 2001 revealed an extraordinarily low rate of thromboembolism (one case in Ͼ500 randomly assigned patients who were followed for Ͼ2000 patient-years). [23][24][25][26][27][28][29] Subtle selection forces operating at the enrollment level may have contributed to this finding. Natural history studies of untreated patients have also noted a low prevalence of thromboembolism in membranous nephropathy.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…A survey of all such trials reported between 1979 and 2001 revealed an extraordinarily low rate of thromboembolism (one case in Ͼ500 randomly assigned patients who were followed for Ͼ2000 patient-years). [23][24][25][26][27][28][29] Subtle selection forces operating at the enrollment level may have contributed to this finding. Natural history studies of untreated patients have also noted a low prevalence of thromboembolism in membranous nephropathy.…”
mentioning
confidence: 65%
“…A possible argument against "routine" prophylactic anticoagulants in idiopathic membranous nephropathy is that none of the randomized therapeutic trials in membranous nephropathy reported between 1979 and 2001 required that enrolled patients be routinely treated with prophylactic anticoagulants. [23][24][25][26][27][28][29] Because ethical considerations demand that participants in such trials receive standard of care, one would have to conclude that prophylactic anticoagulation of patients with membranous nephropathy (and by inference other patients with nephrotic syndrome) has not yet reached a uniform level of standard of care.…”
mentioning
confidence: 99%
“…The design and conduct of therapeutic studies for treatment of MGN remains a challenge because of its relatively slow evolution and highly variable natural history. Long-term follow-up publications of randomized controlled trials (RCTs) on cytotoxic therapy have demonstrated a reduction of ESRD in some (4,5) but not all studies (6). The effect of calcineurin inhibitors on remission of proteinuria is clear, but their effect on renal survival is uncertain (7).…”
Section: Introductionmentioning
confidence: 99%
“…Following this, a variety of immunosuppressive strategies have been explored in IMN patients with underlying renal insufficiency at high risk of progression to ESRD. Two large controlled trials demonstrated improved renal survival with alkylating agents in combination with steroids (10,11). Additionally, cohort studies confirmed the benefits of cytotoxic therapies, with cyclophosphamide being the preferred agent (12)(13)(14).…”
mentioning
confidence: 79%